2020
DOI: 10.1002/adsu.202000085
|View full text |Cite
|
Sign up to set email alerts
|

Novel Solvent Systems for Biomass Fractionation Based on Hydrogen‐Bond Interaction: A Minireview

Abstract: cellulose (30-50 wt%), hemicellulose (20-35 wt%), and lignin (15-30 wt%). [3] CO -C bonds are the main connection bond in the components, but between different components hydrogen bond is the main connection. [2b,4] Cellulose is the most abundant component composed by d-glucose units linked to each other via β-1,4-glycosidic bonds, a certain amount of cellulose shows ordered crystal structure. [5] Hemicellulose is composed with various polymerized monosaccharides, mainly are C5 (xylose, arabinose) and C6 sugar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 180 publications
(211 reference statements)
0
7
0
Order By: Relevance
“…114 Current research has been searching for novel sustainable solvents for biomass fractionation as an alternative for this alkaline treatment. 115 In this regard, natural deep-eutectic solvents (NADES) show promise as sustainable recyclable biomass fractionation agents as certain NADES can dissolve lignin and hemicellulose. 116 Only one study reported the treatment of CI with NADES, 65 specifically choline chloride/malic acid.…”
Section: ■ Valorization Of Spent Common Ivy Residuementioning
confidence: 99%
“…114 Current research has been searching for novel sustainable solvents for biomass fractionation as an alternative for this alkaline treatment. 115 In this regard, natural deep-eutectic solvents (NADES) show promise as sustainable recyclable biomass fractionation agents as certain NADES can dissolve lignin and hemicellulose. 116 Only one study reported the treatment of CI with NADES, 65 specifically choline chloride/malic acid.…”
Section: ■ Valorization Of Spent Common Ivy Residuementioning
confidence: 99%
“…The determination of klason lignin and acid-soluble lignin contents was based on a two-step hydrolysis with sulfuric acid, and then, the resulting hydrolyzed products were used for carbohydrate content determination by high-performance liquid chromatography (HPLC), using a Knauer instrument equipped with a refractive index (RI) detector and a Rezex ROA-organic acid H column from Phenomenex. Aer these determinations, the removals of the main wood components (cellulose, xylan and lignin) obtained aer the pretreatments were calculated based on eqn (2).…”
Section: Composition and Characterization Of Treated And Untreated Woodmentioning
confidence: 99%
“…Using this DES, higher delignication yields could be achieved with less wood dissolution, which means that The treated wood samples that showed a delignication yield higher than 60% (Fig. 3) were selected for carbohydrate content determinations, which enabled the calculation of cellulose and xylan removals by eqn (2). The detailed compositions of these treated woods and untreated wood, as well as the removals of the main wood components obtained aer the pretreatments, are presented in Table 1.…”
Section: Composition and Characterization Of Treated Wood (Celluloserich Material)mentioning
confidence: 99%
See 2 more Smart Citations